2017
DOI: 10.24840/2184-0954_001.001_0003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the psychosocial risk at work as the task of socially responsible companies

Abstract: Although corporate social responsibility is a permanent feature of activities of many companies, only a few companies can show a strategic approach and use complex solutions. It is emphasized that factors which could cause a positive change are institutional incentives such as tax benefits, and a bigger involvement of stakeholders, mostly employees. As far as providing hygienic working conditions is concerned, one must focus on better connecting occupational health and safety (OHS) with positive targets of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, some suggest that having a healthy organization (and healthy work) might be more expensive in a short-term (and in the context maximizing profits), the potential long-term consequences of employee mental well-being might be more grave due to costs to health care systems, family and society ( Hassard et al , 2014 ; Gordon and Schnall, 2017 ). CSR presents a unique opportunity for business organizations to develop frameworks for management and possible reduction of psychosocial risks (through improvement of workplace psychosocial environment) at the employee and organizational levels ( Jain et al, 2011 ; Sadlowska-Wrzesinska, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some suggest that having a healthy organization (and healthy work) might be more expensive in a short-term (and in the context maximizing profits), the potential long-term consequences of employee mental well-being might be more grave due to costs to health care systems, family and society ( Hassard et al , 2014 ; Gordon and Schnall, 2017 ). CSR presents a unique opportunity for business organizations to develop frameworks for management and possible reduction of psychosocial risks (through improvement of workplace psychosocial environment) at the employee and organizational levels ( Jain et al, 2011 ; Sadlowska-Wrzesinska, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…35 CSR is seen as providing a unique platform for business to reduce psychosocial risks in the workplace through implementing strategies to improve the psychosocial environment of the organization. 36,37 A US study by Fairlie and Svergun 38 found that CSR perceptions were positively associated with work satisfaction and appeared to directly buffer both depression symptoms and turnover intentions, through mediating job satisfaction and organizational commitment. CSR strategies in the workplace are also expected to help promote wellness programs that include activities related to health behavior change (e.g.…”
Section: Introductionmentioning
confidence: 99%